2020
DOI: 10.3390/md18090457
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Repertoire of the Red Sea

Abstract: Marine natural products have achieved great success as an important source of new lead compounds for drug discovery. The Red Sea provides enormous diversity on the biological scale in all domains of life including micro- and macro-organisms. In this review, which covers the literature to the end of 2019, we summarize the diversity of bioactive secondary metabolites derived from Red Sea micro- and macro-organisms, and discuss their biological potential whenever applicable. Moreover, the diversity of the Red Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 124 publications
(237 reference statements)
1
18
0
Order By: Relevance
“…From coral-associated organisms, 300 biologically active substances with cytotoxic, antiparasitic, antibacterial, antiinflammatory activities have been isolated (Hou et al, 2019). These compounds are studied as potential anti-tumour and antiviral preparations, including against SARS-CoV-2 and HIV (El-Hossary et al, 2020;Zahran et al, 2020). Many bioactive products (terpenoids, sesquiterpenes, diterpe-nes, steroids and many other) are produced by soft corals and are promising objects for the development of various pharmaceutical preparations (Sang et al, 2019).…”
Section: Marine Organisms Producing Cytotoxic Compoundsmentioning
confidence: 99%
“…From coral-associated organisms, 300 biologically active substances with cytotoxic, antiparasitic, antibacterial, antiinflammatory activities have been isolated (Hou et al, 2019). These compounds are studied as potential anti-tumour and antiviral preparations, including against SARS-CoV-2 and HIV (El-Hossary et al, 2020;Zahran et al, 2020). Many bioactive products (terpenoids, sesquiterpenes, diterpe-nes, steroids and many other) are produced by soft corals and are promising objects for the development of various pharmaceutical preparations (Sang et al, 2019).…”
Section: Marine Organisms Producing Cytotoxic Compoundsmentioning
confidence: 99%
“…In the recent couple of decades, intensive drug discovery research shed the light on the Red Sea marine invertebrates and its bioactive compositions. Several bioactive metabolites with unique chemical scaffolds were isolated, identified and showed promising pharmacological activities from the Red Sea marine life (El-Hossary et al, 2020). Biological activity herein is referred to in case of on any early experimental to late clinical evidence for potential use in the treatment of any human disease.…”
Section: Rationalementioning
confidence: 99%
“…In addition, polyP has been shown to have synergistic anti-viral effects in combination with the anti-inflammatory agent dexamethasone or the anti-oxidant compound quercetin. Furthermore, many studies have shown that several marine metabolites isolated from scleractinia related organisms, sponges and algae can interact with the main protease of Sars-CoV-2, M pro [ 13 , 14 , 15 , 26 , 27 , 28 ]. M pro is a crucial protein enzyme of the virus and has a critical role in mediating the replication and transcription of the viral particles, making it a potential drug target against the virus [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%